Performance evaluation of nine reference centers and comparison of DNA extraction protocols for effective surveillance of Leishmania-infected Phlebotomine sand flies: Basis for technical recommendations. - Jorian Prudhomme; Aymeric Delabarre; Bulent Alten; Umut Berberoglu; Eduardo Berriatua; Gioia Bongiorno; José Manuel Cristovao; Maya Davidovich-Cohen; Trentina Di Muccio; Ozge Erisoz Kasap; Eleonora Fiorentino; Oscar D Kirstein; et al. (PLoS Neglected Tropical Diseases)
Background Leishmaniasis, caused by Leishmania protozoan parasites transmitted by Phlebotomine sand flies, is a significant public health concern in the Mediterranean basin. Effective monitoring of Leishmania-infected sand flies requires standardized tools for comparing their distribution and infection prevalence. Consistent quantitative real-time PCR (qPCR) parameters and efficient DNA extraction protocols are crucial for reliable results over time and across regions. However, the absence of standardized technical recommendations for Leishmania DNA detection hinders effective surveillance. This study aimed to compare different DNA extraction protocols and conduct a qPCR-based External Quality Assessment (EQA) through a multicenter study involving nine reference laboratories, with a focus on optimizing Leishmania DNA detection in sand fly. Methodology/principal findings EQA samples consisted of Leishmania infantum and L. major species, at concentrations ranging from 101 to 104 parasites/mL. All but one center detected all concentrations, demonstrating strong diagnostic proficiency. The ability to detect low concentrations highlighted the robustness of the qPCR assay used, though variations in Cq values indicated differences in sensitivity related to technical capabilities or DNA extraction kit performance. A comparative analysis of seven DNA extraction methods identified the EZ1 DSP Virus Kit and QIAamp DNA mini-kit as the most efficient, supporting their use in standardized protocols. The study also assessed the effects of lyophilization and shipment conditions, showing no significant compromise in Leishmania detection despite slight variations in Cq values. Experimentally infected sand flies were included to simulate field conditions, and all centers successfully detected positive samples with varying Cq values, probably reflecting differences in infection load. Conclusion and significance This study emphasizes the importance of standardized DNA extraction protocols and continuous quality assurance for accurate Leishmania DNA detection. The results highlight the superior performance of certain extraction kits and the need for ongoing technical training, essential for reliable leishmaniasis surveillance, particularly in field settings with low infection densities.